2023
DOI: 10.3390/w15091694
|View full text |Cite
|
Sign up to set email alerts
|

Remote Sensing Monitoring of Soil Salinity in Weigan River–Kuqa River Delta Oasis Based on Two-Dimensional Feature Space

Abstract: Soil salinization is a serious resource and ecological problem globally. The Weigan River–Kuqa River Delta Oasis is a key region in the arid and semi-arid regions of China with prominent soil salinization. The saline soils in the oasis are widely distributed over a large area, causing great harm to agricultural development and the environment. Remote sensing monitoring can provide a reference method for the management of regional salinization. We extracted the spectral indices and performed a correlation analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Salinization in arid regions becomes more severe during spring due to soil thawing, temperature increases, and evaporation [1,10]. Remote sensing satellite interpretation can effectively detect salt accumulation on the surface, which appears as white [11,44]. However, the ground surface is intricate, especially in areas with intense human activities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Salinization in arid regions becomes more severe during spring due to soil thawing, temperature increases, and evaporation [1,10]. Remote sensing satellite interpretation can effectively detect salt accumulation on the surface, which appears as white [11,44]. However, the ground surface is intricate, especially in areas with intense human activities.…”
Section: Discussionmentioning
confidence: 99%
“…Ma and Tashpolat [44] 4 Salinity index 1 S1 S1 = B/R Abbas and Khan [45] Ground Indicator Notes: in the formula, B represents blue band, G represents green band, R represents red band, NIR represents near-infrared band.…”
Section: Satellite Image and Other Spatial Data Processingmentioning
confidence: 99%
“…The research showed an increasing trend in salinization intensity between 1984 and 2022 due to the inadequate agricultural systems adopted. The authors of [154] extracted Sentinel-2 MSI-based indices to monitor soil salinity in a typical saline zone in the Weigan River-Kuqa River Delta Oasis. The study proved that using remote sensing-based monitoring models in this context is fundamental to comprehensively grasp the salinization magnitude and enhance land management practices on the watershed scale.…”
Section: Challenges In Salinization Mappingmentioning
confidence: 99%
“…The Weigan River irrigation district (Figure 1) is located in the alluvial plain in the middle and lower reaches of the Weigan River Basin in Xinjiang. It is flat and is mainly distributed as a quaternary pore water-bearing system [1]. The aquifer groups are strata consisting of pebble gravel, sandy gravel, and single-structure driftstone, with an uncovered thickness in the range of 80-150 m, It is a strongly permeable stratum with very good permeability and water enrichment, categorized as the diving type.…”
Section: Overview Of the Study Areamentioning
confidence: 99%
“…The Weigan River, located in the Aksu Region of Xinjiang, China [1], is one of the important sources among the "Nine Sources and One Mainstream" in the Tarim River basin. The Weigan River basin has an irreplaceable ecological service function, and its ecological stability plays a key role in ensuring water resources for the natural and artificial ecosystems of the whole Tarim River basin [2].…”
Section: Introductionmentioning
confidence: 99%